Comparação de custos da superestrutura e vedação da alvenaria estrutural comparada à alvenaria convencional com foco em habitações populares em Campo Mourão – PR - Schmitz, Guilherme Fochi (2023)
This work was developed with the intention of comparing the costs involved in the construction of popular residences of conventional masonry with reinforced concrete and structural masonry. The comparison seeks to show which construction system brings the lowest implementation cost, taking into account the materials and labor. For the conclusion of the study, a subdivision of the systems developed in stages was made, with the intention of bringing to the study only the parts that were exclusive to each one of them. After defining the expected stages, the projects developed in reinforced concrete and in structural masonry with concrete blocks of a previously built residence in the city of Campo Mourão-PR were prepared. In this way, it was possible to obtain the quantities of materials from the projects and budget them according to a SINAPI table, thus demonstrating the cost difference of each analyzed system and its representation in the final value of the work